Circling the square: Indigenizing the Dissertation (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
Abstract:Through tradition and standardization, the structure of the dissertation template has ‘boxed in’ a colonial standard whilst ‘cornering’ ways of knowing that cannot be expressed within these limits. But within these corners ideas huddle desperately together, preserving valuable embers of knowledge, conserving strength to ignite a fire to round these corners to closer resemble a circle, forcing dialogue between disparate world-views (Ermine, 2007).The Doctoral Forum at the Queensland University of Technology [QUT] in Australia brought together an Aboriginal PhD candidate from Australia and an Indigenous PhD candidate from Canada. Discussion about the limitations of the standard dissertation format arose.  While researching in diverse disciplines, we found we shared experiences of constraint and a kind of tug-of-war to address the requirements of the institution while privileging our positionality and standpoint as Indigenous peoples; speaking back to the dominant voices of the coloniser.  We reflected on how the template acted to privilege Western institutional constructs and how dominant colonial structures suppress land-based methodologies, creativity, and holism. Through our critical dialogues, we recognise that to morph the ‘square’ of standardization, we must nourish an openness towards multiple ways of knowing and doing through a delicate balance of decolonizing and Indigenizing (Pratt, Louis, Hanson & Ottmann, 2018). This paper will address how these two grad students are blurring the boundaries of the standardized dissertation structure. Through critical dialogue, the colonial structures that ‘box’ us in, providing a means for the previously cornered and marginalized voices to be heard.